(untitled) (El-Wahat Journal for Research and Studies, 2017)
The book "Meanings of the Quran" by Abu Zakariaalfura’ is the source for which the books were published as the grammar of the Kufayn grammar. alfura’ was taken from the Quranic text as a sample for its grammatical analyzes and grammatical explanations. Many views were shed on this book in many of the language, grammar. Unlike Albasriiyne, It has been distinguished by opinions in this field, reflecting the thinking that added distinction to the kufi doctrine, where it expanded on the semantic factors. Many grammatical meanings were attributed to the work in the vocabulary. Keywords - alfura’, verbal factor , semantic factor, disagreement, exchange, approximation, abstraction.